2020
DOI: 10.3390/genes11010097
|View full text |Cite
|
Sign up to set email alerts
|

Reworking GWAS Data to Understand the Role of Nongenetic Factors in MS Etiopathogenesis

Abstract: Genome-wide association studies have identified more than 200 multiple sclerosis (MS)-associated loci across the human genome over the last decade, suggesting complexity in the disease etiology. This complexity poses at least two challenges: the definition of an etiological model including the impact of nongenetic factors, and the clinical translation of genomic data that may be drivers for new druggable targets. We reviewed studies dealing with single genes of interest, to understand how MS-associated single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 76 publications
1
4
0
Order By: Relevance
“…For these reasons, using powerful but indirect methods (such as population genetics and immunology) to study the role of latent EBV in MS pathophysiology may yield valuable clues as to the nature of the pathology. Observations that many of the significant MS SNP-associations overlap with EBNA-2 transcription factor binding sites, for example, is interesting because this agrees with observations that anti-EBNA2 antibodies are part of the subset of EBV proteins that show a raised antibody profile in MS ( 23 , 76 79 ). If these studies are interpreted as converging on a role for EBNA-2, then this gives an insight into the nature of the dysregulation of latency, as EBNA-2 is an essential for regulating viral latent gene expression and for EBV-driving lymphocytes into the cell cycle.…”
Section: Epstein Barr Virus: a Master Epigenetic Manipulator Of B Cellssupporting
confidence: 71%
“…For these reasons, using powerful but indirect methods (such as population genetics and immunology) to study the role of latent EBV in MS pathophysiology may yield valuable clues as to the nature of the pathology. Observations that many of the significant MS SNP-associations overlap with EBNA-2 transcription factor binding sites, for example, is interesting because this agrees with observations that anti-EBNA2 antibodies are part of the subset of EBV proteins that show a raised antibody profile in MS ( 23 , 76 79 ). If these studies are interpreted as converging on a role for EBNA-2, then this gives an insight into the nature of the dysregulation of latency, as EBNA-2 is an essential for regulating viral latent gene expression and for EBV-driving lymphocytes into the cell cycle.…”
Section: Epstein Barr Virus: a Master Epigenetic Manipulator Of B Cellssupporting
confidence: 71%
“…Another level of complexity in the virus-host interplay is represented by the respective genomic variability. Single nucleotide polymorphisms (SNPs) have been associated with MS over time, and increasing evidence on this topic has been obtained thanks to genome-wide association studies [38][39][40] . This high-throughput approach led to the discovery (and in some cases confirmation) of SNPs located in DNA sequences coding for proteins or regulatory regions with a potential impact on gene expression and protein-protein interactions [41] .…”
Section: Ebvmentioning
confidence: 99%
“…Most of the described associations, however, show a modest odds ratio (OR) and explain close to half of its heritability [ 1 , 2 ], HLA (in particular, the HLA-DRB1*15:01 haplotype) being the only one that has shown a strong association with MS risk [ 1 ]. It has been suggested that, together with genetic predisposition, some environmental factors, gene–environment, and environment–environment interactions, including smoking, infections (mainly Epstein–Barr virus seropositivity or exposure), low sun exposure/low vitamin D levels, and obesity may be related to the etiopathogenesis of MS and with MS onset and progression [ 3 , 4 , 5 ]. Since it has been suggested that oxidative stress is closely related to inflammation (for example, in inflammatory conditions, immune cells can liberate reactive oxidant substances leading to oxidative stress and, on the other hand, the oxidative damage produced by free radicals can induce an inflammatory response through the Toll-like receptors and inflammasomes) [ 6 , 7 ], with MS being a prototype of inflammatory diseases, oxidative stress could also play a role in the etiopathogenesis of MS. Figure 1 depicts the possible interaction between the different mechanisms proposed in the etiopathogenesis of MS, including oxidative stress.…”
Section: Introductionmentioning
confidence: 99%

Oxidative Stress Markers in Multiple Sclerosis

Jiménez-Jiménez,
Alonso-Navarro,
Salgado-Cámara
et al. 2024
IJMS